Transvenous ethanol sclerotherapy of feeding arteries for treatment of a dural arteriovenous fistula. (20th July 2016) - Alexander, Matthew David; Halbach, Van; Nicholson, Andrew; Settecase, Fabio; Darflinger, Robert J; Amans, Matthew R
Abstract : Dural arteriovenous fistulas (DAVFs) can be complex lesions that require a well trained eye for proper characterization and management decisions. With numerous possible arteries to supply and veins to drain them, DAVFs are often complex lesions. To best treat these complex lesions, the neurointerventionalist should be adept at treating them with multiple techniques. This report describes a unique case in which a DAVF was treated with arterial sclerotherapy using ethanol from a transvenous approach.